Discrete Mathematics again

  • #1
:confused: Construct a formal proof of the theorem:

If (p-> q), (neg [r] -> s), and (neg [q] V neg , then (p-> r).

[refer to table of logical equivalences (p62) and the table of logical implication (p62)]The tables are in the textbook Kenneth Ross, 5th edition, Discrete Math's.

First I have to construct the proof line: I am gessing that the hypotheses are like this, but am not sure for their order:
(neg [r] -> s) /\ (p -> q) /\ (neg [q] V neg ) => (p -> r)

Then I need to make the "formal proof of it" using the tables.

Please someone help me with any sugestion how to keep going with this problem.
Thank you:
 

Answers and Replies

Related Threads on Discrete Mathematics again

  • Last Post
Replies
2
Views
2K
  • Last Post
Replies
4
Views
782
  • Last Post
Replies
6
Views
4K
  • Last Post
Replies
3
Views
4K
  • Last Post
Replies
2
Views
4K
  • Last Post
Replies
0
Views
1K
Replies
11
Views
9K
Replies
1
Views
9K
  • Last Post
Replies
3
Views
1K
Replies
1
Views
2K
Top